PENGARUH HARGA, KUALITAS LAYANAN DAN PROGRAM PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BERKELANJUTAN - Uswatun Chasanah; Muhammad Fauzan (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
This study examined the effect of price, service quality and promotion on sustainablepurchasing decisions. The sample used was 60 respondents with the criteria ofrespondents who used Mamochi products in Yogyakarta. The data was collected usingnon probability sampling method with purposive sampling technique. The results of thevalidity test with the Pearson correlation criteria> 0.254 (r table), showed that all indicatorswere valid, as well as the reliability test with Cronbach's alpha> 0.6. The results of themediation test show that consumer satisfaction mediates the effect of price on repurchasedecisions, while the quality of service and promotion programs have an effect onrepurchase decisions not mediated by customer satisfaction. As for partial testing of pricevariables, service quality has an effect on satisfaction, while promotion has no effect.Likewise, the variables of price, promotion and customer satisfaction have an effect on repurchasedecisions, while service quality has no effect on re-purchase decisions. For thesimultaneous test results, price variables, service quality and promotion have an effect oncustomer satisfaction.